CHALLENGES FACED BY HEALTH CARE WORKERS’ PERFORMANCE IN THE INTENSIVE CARE UNIT OF ST. MARY’S HOSPITAL LACOR - Agenonga, Lawrence; Ssemambo, Nassanga Teddy (Student’s Journal of Health Research Africa, 2023)
Background: In Uganda the burden of critical illness is overwhelming with an unmatched number of ICU beds which was estimated to be at one per a million population with a few number of health care providers, this led to many patients’ deaths because of the lack of material and trained human resources to provide care. Therefore, the purpose of this study was to determine the challenges faced by healthcare workers’ performance in the intensive care unit of St. Mary’s Hospital Lacor, Gulu District. Methodology: The study employed a descriptive cross-sectional design implying quantitative methods of data collection and a self-administered questionnaire to collect data from a sample of 30 health workers who were sampled using a convenient sampling method. Data was collected from respondents after seeking consent from them analyzed and entered manually into the computer using Microsoft Excel Office programs 2016 which presented it in fom1 of tables, graphics, and pie-charts. Results: The majority 21(70%) revealed that they do not feel happy working in the ICU, 19(63.3%) experienced some family-related issues, and 25(83.3%) reached home late due to a heavy workload. 27(90%) said that they were not offered accommodation at the facility, 20(74%) mentioned that the distance was l-5km and 17(56.6%) revealed that conditions were not pleasing. Conclusion: The findings revealed challenges faced by healthcare workers in the ICU and highlighted job satisfaction, family-related issues, workload, staffing levels, accommodation, motivation, and incentives. Recommendation: The ministry should ensure the provision of adequate resources, support, and incentives which could potentially improve job satisfaction, performance, and overall well-being of health workers, leading to better patient care outcomes in the ICU setting.